2009
DOI: 10.1128/aem.02447-08
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Basis for the Inhibitory Effects of Organic and Inorganic Salts on the Growth of Pectobacterium carotovorum subsp. carotovorum and Pectobacterium atrosepticum

Abstract: Twenty-one salts were tested for their effects on the growth of Pectobacterium carotovorum subsp. carotovorum and Pectobacterium atrosepticum. In liquid medium, 11 salts (0.2 M) exhibited strong inhibition of bacterial growth. The inhibitory action of salts relates to the water-ionizing capacity and the lipophilicity of their constituent ions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…The reason for reduced growth in treated samples might be as CaCl 2 is a type of salt that elevates osmolality due to salt addition. This may trigger the osmoregulatory process and diminished bacterial development (Yaganza et al 2009).…”
Section: Microbial Growthmentioning
confidence: 99%
“…The reason for reduced growth in treated samples might be as CaCl 2 is a type of salt that elevates osmolality due to salt addition. This may trigger the osmoregulatory process and diminished bacterial development (Yaganza et al 2009).…”
Section: Microbial Growthmentioning
confidence: 99%
“…This will eliminate the substrate supplies in the cells of microorganisms, which will rapidly slow down the metabolism of the microorganisms and inhibit their growth on the bread surface. 9,22,23 Generally, it is expected that a good dispersion of antimicrobial agents can enhance the antimicrobial activity in the composite films. [68][69][70] Well-dispersed antimicrobial agents have a higher probability of contacting microorganisms and increases the chance of acidity diffusion through the plasma membrane and generating intracellular acidification in microorganisms.…”
Section: Antimicrobial Activitiesmentioning
confidence: 99%
“…Further, SP addition may trigger the osmoregulatory process, causing an increase in maintenance metabolism and a reduction in the overall microorganism growth. 9,22,23 Soares et al succeeded in minimizing the microbial growth on bread by incorporating SP into cellulose acetate films via solution casting. 24 However, the solution casting method is an energy-intensive process and is characterized by low production speed, extra energy costs for solvent recovery, and large investments required for facilities for handing solvents.…”
mentioning
confidence: 99%
“…Several potential mechanisms for the inhibitory effect of PTB on pathogens have been described. Yaganza et al proposed that elevated osmolality caused by inorganic salts may trigger increased maintenance metabolism and, therefore, inhibit bacterial reproduction [7]. Ahmed et al suggested that the pH conditions of the PTB solution disrupt cell integrity and, therefore, have an adverse effect on the bacterial population [8].…”
Section: Introductionmentioning
confidence: 99%